Pahang Today - Big 2000 'Economic and Industrial Growth' - Abu Zarin, Hasmah; Bujang, Ahmad Ariffian (2000)
With the advancement of technology in the agricultural and industrial arena, land reform can be related to the economic development which is frequently identified with economic growth that is the average annual rate of increase in real output per capita.